Application of farming methods for Increasing Children's Naturalist Intelligence - Yanuarsari, Revita; Octrianty, Evi; Nurmilah, Ulpah (Indonesian Journal of Adult and Community Education, 2020)
This research is motivated by the low application of farmingmethods in improving naturalist intelligence of children aged 4-5years in RA Lu'lu, West Bandung Regency, this is due to severalfactors including children littering, picking plants at will, andabandoned plants that have withered. The purpose of this study wasto determine that the application of agricultural methods canimprove naturalist intelligence. This research is a collaborativeclassroom action research consisting of two cycles. Data collectiontechniques using observation, documentation and non-tests. Whilethe instrument used was the observation sheet. The results showedthat there was an increase in naturalist intelligence after using thefarming method.